Bidding despite corruption: evidence from Honduras. Issue 4 (17th August 2021) - Sabet, Daniel M.
Abstract : Purpose: In addition to lower value for money and the loss of trust in government, procurement corruption threatens to produce a vicious cycle whereby honest firms self-select out of public procurements, further increasing corruption and decreasing value for money. This paper aims to explore this vicious cycle hypothesis. Design/methodology/approach: This paper uses a survey of businesses registered with the procurement regulator in Honduras, a country with high grand corruption but low levels of administrative procurement corruption. The study uses the survey to test the effects of experiences and perceptions of corruption and personal connections on perceptions of fairness and intention to bid on future procurements. Findings: This study finds that experiences with bribery and the perceived importance of personal and party connections undermine perceptions of fairness, particularly for firms bidding with Honduras's public works agency. While firms that have not bid recently view the process as less merit-based than those that have, the study does not find that perceptions of fairness influence intention to bid in the future as the vicious cycle hypothesis would suggest. Social implications: This research suggests that even firms that are frustrated with procurement irregularities are willing to tolerate them to access government markets. Originality/value: The study benefits from a unique survey of businesses on issues of corruption and connections in a challenging procurement environment.